2022
DOI: 10.4149/neo_2022_211110n1597
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of endometrial cancer organoids establishment by cancer-associated fibroblasts

Abstract: Most endometrial cancers (EC) are diagnosed at an early stage with a favorable prognosis. However, for patients with advanced or recurrent disease, the chemotherapy response rate and overall survival remain poor. A novel in vitro model, tumor organoids, has important value in providing a more individualized treatment plan for tumor patients. However, the slow growth of the established EC organoid seriously hinders the application of EC organoids. Cancer-associated fibroblasts (CAFs), the main component of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Another study has found that removing N2 from the culture medium and adding ROCK inhibitors can promote long-term expansion and cryopreservation of organoids ( Berg et al, 2021 ). Wu et al optimized the current EC-like organs by introducing CAFs isolated from EC lesions ( Wu et al, 2022 ). Based on co-cultivation of CAFs and EC-like organs, they found that CAFs can promote the growth of EC-like organs, possibly by secreting factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study has found that removing N2 from the culture medium and adding ROCK inhibitors can promote long-term expansion and cryopreservation of organoids ( Berg et al, 2021 ). Wu et al optimized the current EC-like organs by introducing CAFs isolated from EC lesions ( Wu et al, 2022 ). Based on co-cultivation of CAFs and EC-like organs, they found that CAFs can promote the growth of EC-like organs, possibly by secreting factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific experimental conditions reported in each study are different and have been specifically listed above. Wu et al optimized the current EC like organs by introducing cancer-associated fibroblasts (CAFs) isolated from EC lesions ( Wu et al, 2022 ). Based on co-cultivation of CAFs and EC-like organs, they found that CAFs can promote the growth of EC-like organs, possibly by secreting factors.…”
Section: Endometrial Cancer (Ec) Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, in vitro studies on endometrial cancer are based on organoid models. By introducing fibroblasts isolated from endometrial cancer lesions to optimize the current endometrial cancer organoids, the disease-related characteristics and cancer-related mutations were studied [ 275 ]. Organoids faithfully reproduce the genotype of the disease, which will be valuable for exploring the proliferative phenotype and the molecular mechanism of cancer development [ 276 ].…”
Section: Microfluidic Chips For Gynecological Diseasesmentioning
confidence: 99%
“…Given that the characteristics of tumor organoids derived from cancer patients faithfully recapitulate the architecture of their original tumor tissues and organoids, cancer-organoid-culture technology has expanded to other types of cancers. Many researchers have established long-term organoid cultures by using primary-colon [ 15 , 44 ], lung [ 45 , 46 , 47 ], esophageal [ 48 ], pancreatic [ 49 , 50 , 51 ], prostate [ 51 , 52 , 53 ], breast [ 30 , 54 , 55 ], stomach [ 56 , 57 ], liver [ 40 , 58 ], and endometrial [ 59 , 60 ] cancer and normal tissues.…”
Section: Cancer Organoid Model Systemsmentioning
confidence: 99%